2017
DOI: 10.3847/1538-4365/aa647a
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Ionizing Continuum: The Main Driver of Broad Absorption Line Variability

Abstract: We present a statistical analysis of the variability of broad absorption lines (BALs) in quasars using the large multi-epoch spectroscopic dataset of the Sloan Digital Sky Survey Data Release 12 (SDSS DR12). We divide the sample into two groups according to the pattern of the variation of C iv BAL with respect to that of continuum: the equivalent widths (EW) of the BAL decreases (increases) when the continuum brightens (dims) as group T1; and the variation of EW and continuum in the opposite relation as group … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 63 publications
2
69
1
2
Order By: Relevance
“…Such a trend is different from what is typically observed in luminous quasars, for which the weakening of BAL trough is often accompanied with the brightening of continuum (e.g., Wang et al 2015;He et al 2017;Pinto et al 2018). This may be explained by the different ionization states between WPVS 007 and quasars.…”
Section: Change Of Ionization State and Bal Trough Strengthcontrasting
confidence: 88%
See 1 more Smart Citation
“…Such a trend is different from what is typically observed in luminous quasars, for which the weakening of BAL trough is often accompanied with the brightening of continuum (e.g., Wang et al 2015;He et al 2017;Pinto et al 2018). This may be explained by the different ionization states between WPVS 007 and quasars.…”
Section: Change Of Ionization State and Bal Trough Strengthcontrasting
confidence: 88%
“…Instead, the coordinated correlation can be easily explained if the BAL variability is photoionization-driven (e.g., Hamann et al 2011;FilizAk et al 2012FilizAk et al , 2013Wang et al 2015;He et al 2017). As pointed out in Section 4.1, the C iv and Si iv column densities decrease when the source becomes fainter.…”
Section: Coordination Between Outflow Velocity and Agn Luminositymentioning
confidence: 99%
“…Our initial sample consists of 2005 BAL quasars constructed by He et al (2017) from the SDSS-I/II/III. Among them, there are 46 quasars have at least fiveepoch observations and a signal-to-noise ratio (S/N) level of S/N>10 in one-epoch observation at least.…”
Section: Sample Selection and Correlation Analysismentioning
confidence: 99%
“…When the absorbing gas are at a relatively low ionization state, the EW of the C IV/Si IV BAL show positive response to the continuum variation, otherwise, the negative response reveals the relatively high ionization state. On the other hand, based on large absorption line samples, statistical studies in both BALs (e.g., Wang et al 2015;He et al 2017) and NALs (Lu et al 2017;Chen et al 2018b) also showed that the variations of intrinsic absorption lines are positively or negatively responded to the alternations of quasar continua. These two kinds of respond suggest that the variable intrinsic absorption lines can be divided into at least two classes: one is highly ionized systems dominated by absorbing gas in high ionization and show negative response to changes of quasar emissions; and the other is lowly ionized systems dominated by absorbing gas in low ionization and show positive response to changes of quasar emissions.…”
Section: Positive Vs Negative Correlationsmentioning
confidence: 99%
See 1 more Smart Citation